Effective tax rates for R&D intangibles - González Cabral, Ana Cinta (OECD Publishing, 2023)
Tax incentives such as intellectual property regimes provide for reduced taxation of the income derived from research, development, and innovation related activities. By doing so, they lower the overall tax burden from investing in certain qualified intangible assets. This paper proposes a methodology to build indicators comparing the effect of income-based tax incentives for R&D and innovation on firms' incentives to make R&D intangible investments. It provides insights into how such incentives affect firms' decisions on whether, where and how much to invest in R&D intangibles. These indicators are used to illustrate the extent to which these tax incentives may create potential distortions to firms' investment, protection and commercialisation decisions. The model is further developed to account for the design changes to such tax incentives introduced by the OECD/G20 Base Erosion and Profit Shifting minimum standard
Keywords: Finance and Investment; Taxation; Science and Technology